Hip dysplasia is not uncommon but frequently overlooked: a cross-sectional study based on radiographic examination of 1, 870 adults. (8th October 2021) - Leide, Rebecka; Bohman, Anna; Wenger, Daniel; Overgaard, Søren; Tiderius, Carl Johan; Rogmark, Cecilia
Abstract : Background and purpose — Hip dysplasia in adults is a deformity in which the acetabulum inadequately covers the femoral head. The prevalence is sparingly described in the literature. We investigated the prevalence in Malmö (Sweden) and assessed whether the condition was recognized in the radiology reports. Subjects and methods — All pelvic radiographs performed in Malmö during 2007–2008 on subjects aged 20–70 years with a Swedish personal identity number were assessed. 1, 870 digital radiographs were eligible for analysis. The lateral center-edge angle (LCEA) and acetabular index angle (AIA) were measured. Hip dysplasia was defined as an LCEA ≤ 20°. Intraclass correlation coefficients (ICC) for intra-observer measurements ranged from 0.87 (AIA, 95% CI 0.78–0.93) to 0.98 (LCEA, CI 0.97–0.99). Results — The prevalence of hip dysplasia (LCEA ≤ 20°) was 5.2% (CI 4.3–6.3), (98/1, 870). There was no statistically significant difference between the sexes for either prevalence of hip dysplasia or mean LCEA. The mean AIA was 0.9° (CI 0.3–1.3) higher in men (4.1 SD 5.5) compared with women (3.2 SD 5.4). The radiologists had reported hip dysplasia in 7 of the 98 cases. Interpretation — The prevalence of hip dysplasia in Malmö (Sweden) is similar to previously reported data from Copenhagen (Denmark) and Bergen (Norway). Our results indicate that hip dysplasia is often overlooked by radiologists, which may influence patient treatment.